1819: Isa Kamari's Perspective on the Establishment of Singapore: (1819: Penubuhan Singapura dari Kaca Mata Isa Kamari) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2015)
The British are said to have "established Singapore" in 1819. At the beginning of that year, Sir Stamford Raffles signed a preliminary agreement with the Temenggung of Johor that allowed him to establish a trading post on the island (Turnbull, 1989: 1). By 1824, the British desire to establish a trading post had given way to the imposition of a treaty that permitted the British to control the whole island. 1819 is also the title of the English translation of Isa Kamari's novel Duka Tuan Bertakhta. Isa is a leading Singapore novelist and the novel deals with the events of those important years. Raffles, the Temenggung and the newly crowned Sultan Hussein of Johor all major roles in the novel. But equally important are the holy man, Habib Nuh, the silat teacher Wan Cantuk, and Munsyi Abdullah, a writer, all of whom give their opinion on the effects of the British colonization of Singapore. This article focuses on the way that Isa presents the loss suffered by the Malay community of Singapore and the implications of that loss for contemporary Malay society in Singapore, rather than just the historical events of 1819.Keywords: establishment of Singapore, Sir Thomas Stamford Raffles, Sultan Hussein, political leadership, opium